SOCIAL GENDER STEREOTYPES AND THEIR IMPLICATIONS IN HINDI - Pande, Anjali (POLISSEMA – Revista de Letras do ISCAP, 2019)
This essay looks at the subtle ways in which gender identities are constructed and reinforced in India through social norms of language use. Language itself becomes a medium for perpetuating gender stereotypes, forcing its speakers to confirm to socially defined gender roles. Using examples from a classroom discussion about a film, this essay will highlight the underlying rigid male-female stereotypes in Indian society with their more obvious expressions in language. For the urban woman in India globalisation meant increased economic equality and exposure to changed lifestyles. On an individual level it also meant redefining gender relations and changing the hierarchy in man-woman relationships. With the economic independence there is a heightened sense of liberation in all spheres of social life, a confidence to fuzz the rigid boundaries of gender roles. With the new films and media celebrating this liberated woman, who is ready to assert her sexual needs, who is ready to explode those long held notions of morality, one would expect that the changes are not just superficial. But as it soon became obvious in the course of a classroom discussion about relationships and stereotypes related to age, the surface changes can not become part of the common vocabulary, for the obvious reason that there is still a vast gap between the screen image of this new woman and the ground reality. Social considerations define the limits of this assertiveness of women, whereas men are happy to be liberal within the larger frame of social sanctions. The educated urban woman in India speaks in favour of change and the educated urban male supports her, but one just needs to scratch the surface to see the time tested formulae of gender roles firmly in place. The way the urban woman happily balances this emerging promise of independence with her gendered social identity, makes it necessary to rethink some aspects of looking at gender in a gradually changing, traditional society like India.